Classical Masculinity and the Spectacular Body on Film - O'Brien, D. author. aut Link
VII, 191 p.
Keywords: The muscle-bound male body is a perennial feature of classically-inflected action cinema. This book reassesses these films as a cinematic form, focusing on the depiction of heroic masculinity. In particular, Hercules in his many incarnations has greatly influenced popular cultural interpretations of manliness and the exaggerated male form.